Designing a self-associated cationic polymer for enhanced compatibility, palatability, and gastric release of cefuroxime axetil - Menjoge, Anupa R.; Kulkarni, Mohan G. (Biomacromolecules, 2007)
Cefuroxime axetil (CA) has exhibited interactions with the polymers hydroxypropyl methylcellulose phthalate, cellulose acetate trimellitate, and Eudragit E resulting in the generation of unacceptable amounts of impurities and degradation. Formulations, which mask the bitter taste of CA and release it immediately in the stomach, have therefore not been possible. In an attempt to overcome the interaction with CA, we report a self-associated cationic polymer (NREP) containing methyl methacrylate (MMA), 2-hydroxy ethylmethacrylate (HEMA), and 4-vinyl pyridine (4-VP). The hydrogen bonding between the pyridine nitrogen and the hydroxyl groups of HEMA results in strong intrachain associations, prevents interactions between NREP and CA, and inhibits degradation of CA. This has been validated by differential scanning calorimetry, Fourier transform infrared spectroscopy, NMR, and high-performance liquid chromatography analysis. These self-associations restrict polymer chain motions, enhance biocompatibility, and lead to a higher T-g, which ensures that NREP does not become tacky in processes involving heat. The judicious choice of the hydrophobic and hydrophilic monomers renders the polymer hydrophobic enough as to mask the bitter taste of CA at near neutral pH. Incorporation of the basic monomer 4-VP ensures rapid dissolution of the polymer and release of CA at the acidic pH prevalent in the stomach. The work indicates an approach to design pH-sensitive polymers for dosage forms that meet the pharmacokinetic requirements of the drug.